PENGARUH VOLUME PERDAGANGAN SAHAM, DIVIDEND YIELD, EARNING VOLATILITY, FIRM SIZE, DAN NILAI TUKAR TERHADAP VOLATILITAS HARGA SAHAM (Studi Empiris Prusahaan yang Terdaftar Indeks LQ45 Periode 2016-2020) - Donna Rizky Safrani; Eny Kusumawati (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study was to examine the effect of stock trading volume, dividend yield, earning volatility, firm size, and exchange rate on stock price volatility. The sample data used in the study amounted to 114 of 23 companies indexed by LQ45 in the 2016-2020 research period. Analysis of the data used in this study is multiple linear regression analysis. Based on the research, it can be concluded that stock trading volume has a positive and significant effect on stock price volatility, firm size has a significant negative effect on stock price volatility, while other variables have no effect on stock price volatility.